Human - non-human socialities in the city :|an examination of Istanbul’s multispecies histories - Haspolat, Zeynep Gizem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis explores the human – non-human relationships in Istanbul through the examination of particular moments of the city’s multispecies histories. To this end, my research focuses on both the 1910 Hayırsızada Event, throughout which 80.000 dogs were exiled to death on a small island, and the non-human animal politics of the 2010s. My aim is twofold in this exploration: I would like to both contribute to the emerging literature that discusses the role of non-human animals in the formation of the social and engage with the discussions around the need to develop new multispecies ethical frameworks. Methodologically, I explored the Hayırsızada event through archival work and analyzed the 2010’s non-human politics through municipal policies and testimonies of animal volunteers who care for the non-human animals on streets and in the outskirts of the city despite the municipalities policies of exile, confinement, and extermination. In arguing that human histories and socialities cannot be thought independent of the non-human animal histories, the animal volunteers’ ethical claims and the care labor they exemplify emerged also as significant examples to think through the larger questions about finding ways to live and flourish together, as they have become more pressing in the Anthropocene.
Keywords: Human-animal relationships -- Turkey -- Istanbul.; Dogs -- Turkey -- Istanbul -- Anecdotes.